A microstructure study of colloidal gold nanoparticles by X-ray diffraction line profile analysis. (March 2021) - Araújo, J.C.; Iwamoto, W.A.; Monte, A.F.G.; Cabral, Jader S.; Antunes, Andrea; Breener, O.; Estévez-Rams, E.; Lora-Serrano, R.
Abstract: We present the colloidal synthesis of gold nanoparticles (Au NPs) using the chemical reduction of gold precursors by changing the reducing agent (Na3 C6 H5 O7 ) volume. We aimed at achieving different particle sizes, morphologies, and defect structures. The modified process impacted the overall synthesis time and nanoparticles' microstructures. We used X-ray diffraction profile analysis (XPA) and transmission electron microscopy (TEM) to follow the nanoparticles' size and lattice strain details. The NPs' size distributions agree well between the indirect XPA and TEM direct measures. Nanocrystal shapes change from triangular, octahedral, and decahedral to hexagonal plate-like; it shows how the NPs minimize their energy formation by creating defects and well-defined crystallographic directions, including crystal fusion. The combined effects of dislocations, twin boundaries, and surface tension add together to broaden the diffracted line profiles. In particular, the density of dislocation and twin boundaries increase toward the smaller NPs. Highlights: Au nanoparticles with sizes between 15nm and 83 nm were produced optimizing a colloidal process. Regular shapes were obtained by changing the reducing agent concentration. X-ray diffraction line broadening anisotropy is driven by a distorted nanostructure. The densities of twin faults and dislocations are lower for larger particle sizes. Apparent crystallite sizes extracted from XPA are consistent with TEM mean sizes.